Basic Principles of Safeguards by Design - Jeremy Whitlock (Brazilian Journal of Radiation Sciences)
This paper presents basic principles of Safeguards by Design (SBD), whereby the International Atomic Energy Agency (IAEA) provides guidance to State and regional safeguards authorities, designers, equipment providers and prospective purchasers on the importance of taking international safeguards into account when designing or modifying a nuclear facility or process.